Nanodelivery of antiretroviral drugs to nervous tissues - Lawal, Sodiq Kolawole; Olojede, Samuel Oluwaseun; Faborode, Oluwaseun Samuel; Aladeyelu, Okikioluwa Stephen; Matshipi, Matome Nadab; Sulaiman, Sheu Oluwadare; Naidu, Edwin Coleridge Stephen; Rennie, Carmen Olivia; Azu, Onyemaechi Okpara (Frontiers in Pharmacology, 2022)
Despite the development of effective combined antiretroviral therapy (cART), the neurocognitive impairments associated with human immunodeficiency virus (HIV) remain challenging. The presence of the blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BCFB) impedes the adequate penetration of certain antiretroviral drugs into the brain. In addition, reports have shown that some antiretroviral drugs cause neurotoxicity resulting from their interaction with nervous tissues due to long-term systemic exposure. Therefore, the research into the effective therapeutic modality that would cater for the HIV-associated neurological disorders (HAND) and ART toxicity is now receiving broad research attention. Thus, this review explores the latest information in managing HAND using a nanoparticle drug delivery system (NDDS). We discussed the neurotoxicity profile of various approved ART. Also, we explained the applications of silver nanoparticles (AgNPs) in medicine, their different synthesis methods and their interaction with nervous tissues. Lastly, while proposing AgNPs as useful nanoparticles in properly delivering ART to enhance effectiveness and minimize neurocognitive disorders, we hypothesize that the perceived toxicity of AgNPs could be minimized by taking appropriate precautions. One of such precautions is using appropriate reducing and stabilizing agents such as trisodium citrate to reduce silver ion Ag+ to ground state Ag0 during the synthesis. Also, usage of medium-sized, spherical-shaped AgNPs is encouraged in AgNPs-based drug delivery to the brain due to their ability to deliver therapeutic agents across BBB. In addition, characterization and functionalization of the synthesized AgNPs are required during the drug delivery approach. Putting all these factors in place would minimize toxicity and enhance the usage of AgNPs in delivering therapeutic agents across the BBB to the targeted brain tissue and could cater for the HIV-associated neurological disorders and neurotoxic effects of antiretroviral drugs (ARDs).